Toward a green economy in China: current status and perspective in electricity generation - Jorge Morales Pedraza (Academia Green Energy)
China, a leading global energy consumer, is undergoing a significant shift toward a green economy. The main factors driving this shift are ambitious objectives to achieving carbon neutrality and a growing focus on environmental sustainability. This review examines the current status of China’s use of energy resources within the context of the green economy. A review of the published literature was conducted to provide updated data and information on China's energy transition from fossil fuel-based electricity generation to the utilization of renewable energy sources. The discussion concluded that although China relies mostly on fossil fuels, it has made significant progress in renewable energy penetration in the national mix. Wind and solar electricity are growing rapidly, but hydropower dominates. China has demonstrated its commitment to renewable energy by surpassing many other large countries through a rapid investment in clean energy. However, thoughtful policymaking is needed to balance economic growth with environmental protection. This work emphasizes the urgent need to prevent new coal-fired power plants, adopt management rules to permit high renewable energy generation from the national grid, and allow cheap consumer prices to drive consumption and generation. While China’s efforts to become more environmentally friendly are still ongoing, it has become a global leader in sustainable energy.